KEMAMPUAN GURU DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL PADA KURILUKUM MERDEKA BELAJARDI TK IT AN-NAFIS TELUK MENGKUDU - Septi Ayu Syahraini; Nurzannah (Adisam Publisher, 2024)
This research aims to determine teachers' abilities in developing learning media based on local wisdom. This type of research is descriptive qualitative. The subjects of this research were the principal and teachers of the An-Nafis Teluk Mengkudu IT Kindergarten. The object of this research is to describe teachers' abilities to develop learning media based on local wisdom. Data collection techniques were carried out using observation, interviews and documentation. The results of the research are that teachers are able to develop learning media based on local wisdom in the independent learning curriculum by utilizing the surrounding environment and making learning media that is easy to understand, in order to create a fun and not boring atmosphere for children and also educators in carrying out activities in the classroom, in developing media learning based on local wisdom, teachers apply traditional game media.